Impoliteness Strategies Used in the Movie Pearl Harbor - Devi Tri Romadhoni; Rahmaditya Khadifa Abdul Rozzaq Wijaya; Aris Hidayatulloh (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Impoliteness is defined as communicative behavior that is intended to cause offense, social disruption, or emotional harm. The description that occurs not only in social life but can found in the film, which used by the characters. Culpeper divided three functions of impoliteness there are affective, coercive, and entertaining. This research aims to analyze the functions of impoliteness which found in the movie Pearl Harbor.The method used to analyze and collecting data which found and contained in the Pearl Harbor movie through descriptive qualitative methods, using Spradley 1980 theory. This research used data collection from the dialogues between characters in the movie. The result of this analysis shows that the researcher found three functions of impoliteness proposed by Culpeper. Three functions of impoliteness were found in this movie with two functions having the same data, namely affective and coercive. Because of the war setting so that these two functions are the most suitable to use and researcher also found one function of entertaining. The conclusion of this research that based on the background of war, then in this movie it is very suitable to be researched using impoliteness. In war usually raises conflict and tension where it can lead to impoliteness. The more tension there is in the movie, the more impoliteness is used.